(untitled) (Oratio Directa, 2024)
This study analyzes the political communication strategy, obstacles, and opportunities of the campaign team of Al Haris and Abdullah Sani in the 2020 Jambi gubernatorial election. A mature communication strategy and broad dissemination of political issues were necessary to win the electoral contest. Using a descriptive qualitative approach, the study applies political marketing theory through push, pull, and pass marketing. The campaign team employed face-to-face communication, social media, mainstream and online media, and limited open campaigning. The main internal obstacle was weak coordination and communication among campaign personnel, while the external obstacle involved perceptual distortion among novice voters with limited political education. The candidates' programs, personal appeal, religious and community networks, and political marketing capacity created opportunities to broaden electoral support.